Obtenção de novos sistemas nanoautoemulsificantes a partir do óleo das sementes de Azadirachta indica A Juss e suas aplicações como inibidores de corrosão - Emerenciano, Denise Pofirio (2013)
Corrosion is a natural process that causes progressive deterioration of materials, so, reducing the corrosive effects is a major objective of development of scientific studies. In this work, the efficiency of corrosion inhibition on a AISI 1018 carbon steel of the nanoemulsion system containing the oil of the seeds of Azadirachta indica A. Juss (SNEOAI) was evaluated by the techniques of linear polarization resistance (LPR) and weight loss (CPM), a instrumented cell. For that, hydroalcoholic extract of leaves of A. indica (EAI) was solubilized in a nanoemulsion system (SNEOAI) of which O/W system (rich in aqueous phase). This nanoemulsion system (tested in different concentrations) was obtained with oil from the seeds of this plant species (OAI) (oil phase), dodecylammonium chloride (DDAC) (surfactant), butanol (cosurfactant) and water, using 30 % of C/T (cosurfactant/surfactant), 0.5 % of oil phase and 69.5 % of aqueous phase, and characterized by surface tension, rheology and droplet sizes. This systems SNEOAI and SNEOAI-EAI (nanoemulsion containing hydroalcoholic extract - EAI) showed inhibition efficiencies in corrosive environment in saline (1 %), for the method of LPR with significant value of 70.58 % (300 ppm) to SNEOAI, 74.17 % (100 ppm) and 72.51 % (150 ppm) to SNEOAI-EAI. The best efficiencies inhibitions were observed for the method of CPM with 85.41 % for the SNEOAI (300 ppm) and 83.19 % SNEOAI-EAI (500 ppm). The results show that this formulation could be used commercially for use as a corrosion inhibitor, this research contributed to the biotechnological applicability of Azadirachta indica, considering the large use of this plant species rich in limonoids (tetranortriterpenoids), especially azadirachtin